The Perception of the “Environmental Attributes” of Food Product Packaging and Their Influence on Buyers’ Purchasing Decisions (During The SARS-Cov-2 Pandemic) - Wioletta WRÓBLEWSKA; Dariusz PASZKO; Joanna PAWLAK (Communications of International Proceedings, 2021)
Packaging is a major side issue in the consumption of products, mainly food goods. Therefore, the introduction of more eco-friendly packaging has been one of the strongest trends in the packaging sector in recent years. However, in many markets, the perception of packaging as environmentally friendly is not entirely clear. The purpose of this paper is to assess the perception and importance of the environmental aspects of food product packaging by its purchasers, which might serve to further identify existing barriers or opportunities in their purchase.  Consumers expect environmentally friendly packaging, but this did not correlate with their market behaviour. For nearly 50% of the respondents, food product packaging did not influence their purchasing choices. Also, when given the choice between standard and eco-friendly packaging, the majority of the respondents declared that they would choose the former. The main constraints on purchasing environmentally friendly packaging included price constraints and the availability of eco-friendly packaging, but also situation-related factors, particularly the SARS-CoV-2 pandemic. During the pandemic, the purchasing behaviour of buyers was mainly directed towards the aspect of current health and life protection, pushing the ecological aspect into the background. The level of knowledge of eco-labels placed on food product packaging should be considered insufficient and differentiated by gender, i.e. a lower percentage of the women than the men correctly identified the symbols on the packaging.
Keywords: Eco-Friendly Packaging; Food Product; SARS-Cov-2